RESTRUCTURING OF MOTORCYCLE SALE-BASED FINANCING THROUGH MEDIATION FROM THE PERSPECTIVE OF MASLAHAH MURSALAH - Rabbiyatul Atdawiyah Lubis; Annisa Sativa (Journal Analytica Islamica, 2026)
The development of motorcycle purchases through financing schemes continues to increase, but this has implications for the increased risk of default due to late payments, especially during economic pressures such as the Covid-19 pandemic. This condition demands a settlement mechanism that not only provides legal certainty for financing institutions but also protects consumers so that obligations can still be met without losing the object of financing. This study aims to analyze financing restructuring as a solution to resolve defaults in motorcycle sales and purchase agreements, as well as assess the function of mediation as a dialogue space that produces a new, fair agreement based on the perspective of maslahah mursalah. The study uses a normative juridical method with a statutory and conceptual approach, through a review of the Civil Code, POJK No. 14/POJK.05/2020, and PERMA No. 1 of 2016, accompanied by a study of relevant literature. The results of the study indicate that financing restructuring (rescheduling, reconditioning, and restructuring) is effective in maintaining contract sustainability and reducing potential losses for both parties. Mediation plays a strategic role as a mandatory deliberation mechanism prior to litigation, allowing for proportional adjustments to payment schemes and avoiding protracted conflicts. From a maslahah mursalah perspective, mediation-based restructuring represents a solution that brings benefits, prevents harm, and maintains the socio-economic stability of the parties. These findings confirm that the dialogic-restorative approach is a more humane and relevant model for resolving financing disputes in contemporary legal practice.